Antitumour efficacy of lymphokine-activated killer cells loaded with ricin against experimentally induced lung metastases. - Zanovello, P; Rosato, A; Bronte, V; Mandruzzato, S; Cerundolo, V; Collavo, D (1992)
Adoptive transfer of tumour-specific T lymphocytes loaded with ricin into tumour-bearing mice exerts a transient therapeutic effect against locally induced tumours [Cerundolo et al. (1987) Br J Cancer 55: 413]. As transferred cells preferentially locate in the lung, we studied the therapeutic effect of ricin-loaded, lymphokine-activated killer (LAK) cells on lung metastases induced by M4 or B16-F1 (F1) tumour cell injection. In vitro studies demonstrated that ricin-treated LAK cells were about 100-fold more efficient than untreated LAK cells in inhibiting growth of the ricin-sensitive M4 tumour cell line. This effect was most likely due to the released ricin, as treated and untreated LAK cells inhibited the relatively toxin-resistant F1 cell line to the same extent. Ricin treatment did not alter the tissue distribution of intravenously (i.v.) injected LAK cells, which selectively localized in the lung early after inoculation, whether or not metastases were present. Adoptive transfer experiments showed that ricin-treated LAK cells were significantly more efficient than untreated LAK cells in inhibiting M4- but not F1-induced lung metastases. These results indicate that LAK cells are able to deliver a therapeutic concentration of antineoplastic compounds directly to the lung.